A GIS based planning support system for inclusionary housing profitability optimisation in Cape Town, South Africa - Krause, Philip (Centre for Transport Studies, 2019)
Apartheid era legislation, along with automobile-oriented city planning practices, have left legacies of race/class-linked spatial inequality, and unsustainable land-use transport inter-relationships in post-Apartheid South African cities. Most poor urban communities still live in peripheral settlements, which are far from employment, education, and social opportunities. Consequently, these communities are reliant on public transit services which are inadequate and often unsafe. Despite substantial democratic era public transit investment, this automobile-oriented spatial legacy, rapid urbanisation and a growing middle class have contributed to increased automobile ownership and severe traffic congestion. This, along with inner-city and surrounding precinct regeneration programmes, guided by neo-liberal market-friendly agendas, have contributed towards gentrification and consequent displacement of poorer communities from the few remaining central, but previously affordable, precincts. Intervention is required to halt this trend, and to enable poorer communities’ return to central urban neighbourhoods. Inclusionary housing in private sector housing developments could be one such intervention. Since 2007, national and municipal authorities have devoted resources to developing inclusionary housing policies; over a decade later, none have progressed beyond draft state. A core challenge has been establishing mechanisms that ensure sufficient flexibility to accommodate widely differing market conditions between precincts. Decisions by local authorities/private property developers to grant concessions/pursue projects are influenced by constraining factors applicable to the particular land parcels considered. The ease and rigour of such decision-making at both a policy and implementation level could arguably be enhanced by a GIS (geographic information system) based PSS (planning support system), that is capable of analysing spatial and non-spatial factors on multiple land parcels. This could enable a comparison of the impact that concessions (in exchange for inclusion of affordable units) may have on the financial viability of projects. The research objective of this dissertation was to establish the technical feasibility of developing such a GIS-based inclusionary housing profitability assessment PSS, capable of utilising existing GIS data (maintained by City of Cape Town metropolitan municipality), and which is capable of aiding local authorities and property developers, and ultimately, low-income communities. In conducting this research, a system intending to meet this objective was developed. Through engagement with stakeholders, five case study sites were identified. These were analysed using the system, allowing assessment of their suitability for inclusionary housing, while also allowing for the performance of the system itself to be evaluated. Case study findings suggest that moderately wealthy neighbourhoods are best suited to inclusionary housing projects, as the impact of cross-subsidisation appeared strongest. Project viability was found to be highly sensitive to market conditions, highlighting the importance of using accurate and up-to-date market data. Ultimately, it was concluded that stakeholders see value in the development of a GIS based inclusionary housing PSS, but for the system to truly meet its objective of aiding inclusionary housing policy development and implementation decisions, additional functionality would be required.